2013
DOI: 10.1128/jvi.01863-12
|View full text |Cite
|
Sign up to set email alerts
|

HIV-1 Resistance to Maraviroc Conferred by a CD4 Binding Site Mutation in the Envelope Glycoprotein gp120

Abstract: Maraviroc (MVC) is a CCR5 antagonist that inhibits HIV-1 entry by binding to the coreceptor and inducing structural alterations in the extracellular loops. In this study, we isolated MVC-resistant variants from an HIV-1 primary isolate that arose after 21 weeks of tissue culture passage in the presence of inhibitor. gp120 sequences from passage control and MVC-resistant cultures were cloned into NL4-3 via yeast-based recombination followed by sequencing and drug susceptibility testing. Using 140 clones, three … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
40
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 51 publications
(43 citation statements)
references
References 62 publications
3
40
0
Order By: Relevance
“…However, increasing virus concentration reduced MVC inhibition, suggesting a competition between virus and MVC for CCR5 binding. The potential for competitive MVC and PSC-RANTES inhibition is consistent with the resistance mechanisms observed with different MVC-resistant and PSC-RANTES-resistant viruses (19,20). Overall, we provide here a detailed characterization of inhibition and resistance to the U.S. Food and Drug Administration-approved CCR5 antagonist, MVC, and the CCR5 agonist, PSC-RANTES.…”
supporting
confidence: 78%
See 2 more Smart Citations
“…However, increasing virus concentration reduced MVC inhibition, suggesting a competition between virus and MVC for CCR5 binding. The potential for competitive MVC and PSC-RANTES inhibition is consistent with the resistance mechanisms observed with different MVC-resistant and PSC-RANTES-resistant viruses (19,20). Overall, we provide here a detailed characterization of inhibition and resistance to the U.S. Food and Drug Administration-approved CCR5 antagonist, MVC, and the CCR5 agonist, PSC-RANTES.…”
supporting
confidence: 78%
“…Both the wild-type and the PSC-RANTES-resistant viruses showed similar sensitivities to drugs not targeting the host cell entry step in replication. Finally, all entry inhibitors and each of these viruses (in the present study) have been tested using human PBMCs in the past and to confirm resistance, as observed in the U87 cells (16,19,20,23,27). The present study is designed to carefully define drug mechanism.…”
Section: Resultsmentioning
confidence: 96%
See 1 more Smart Citation
“…For the former, RNA was extracted from plasma samples, and the SIV env gene was then reverse transcribed and PCR amplified from the plasma RNA with the SIV versions of the primers described previously (24). Pyrosequencing of the C2-V3 region was performed on PCR amplicons, i.e., amplified from gp130 env DNA fragments.…”
Section: Methodsmentioning
confidence: 99%
“…Although maraviroc (MVC), which is the first and currently only approved CCR5 antagonist for the treatment of CCR5-tropic (R5) HIV-1 infected patients, and another CCR5 inhibitor, vicriviroc (VCV), can efficiently suppress HIV-1 replication, drug-resistant variants can arise both in vitro and in vivo using drug-bound CCR5 for cellular entry (3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18). The presence of MVC-resistant HIV-1 variants may be due to the outgrowth of pre-existing CXCR4-tropic (X4) HIV-1 viruses (19,20) or the selection of MVC-resistant R5 mutants (12,17).…”
Section: Introductionmentioning
confidence: 99%